PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA PT. HADJI KALLA CABANG BONE - ST. Rahmaniar; Musa, Chalid Imran; Haeruddin, M. Ikhwan Maulana (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine what the effect of organizational culture partially and simultaneously on employee performance. The type of research used is descriptive quantitative. The independent variable in this study is organizational culture while the dependent variable is employee performance. The population in this study were all employees in the office of PT. Hadji Kalla Cabang Bone, while the sample is 58 employees. Data collection was done by using a questionnaire. The data analysis technique used is simple regression analysis using SPSS Version 25 in 2022. The results of the study concluded that the independent variable, namely organizational culture (X) simultaneously or simultaneously affected employee performance (Y) positively and significantly.